Association of Increased Fibrin Turnover and Defective Fibrinolytic Capacity with Leg Atherosclerosis - Cortellaro, M; Cofrancesco, E; Boschetti, C; Mussoni, L; Donati, M B; Catalano, M; Gabrielli, L; Lambardi, B; Specchia, G; Tavazzi, L; Tremoli, E; Turri, M; PLAT Group (Thrombosis and Haemostasis, 1994)
Patients with peripheral arterial disease have a high risk of death from cardiovascular events. As defective fibrinolysis associated with leg atherosclerosis has been suggested as a predisposing factor, we sought a relation among decreased fibrinolysis, the presence of leg atherosclerosis and the incidence of thrombotic events in a case control study nested in the PLAT.Fifty-eight patients with coronary and/or cerebral atherothrombotic disease, free of leg atherosclerosis at Doppler examination, were compared with 50 atherosclerotic patients with leg involvement. High D-dimer (153.0 vs 81.3 ng/ml, p <0.001) and tPA antigen before venous stasis (14.4 vs 11.8 ng/ml, p <0.03), and low tPA antigen (6.7 vs 15.6 ng/ml, p <0.01) and fibrinolytic activity released after venous stasis (fibrinolytic capacity: 113.2 vs 281.4 mm2, p <0.001) were found in patients with leg atherosclerosis. D-dimer and fibrinolytic capacity, in addition to age, were selected by stepwise discriminant analysis as characterizing patients with leg atherosclerosis. Moreover, higher D-dimer and tPA inhibitor characterized patients with leg atherosclerosis who subsequently experienced thrombotic events.These findings constitute evidence of high fibrin turnover and impaired fibrinolytic potential in patients with leg atherosclerosis. Thus impaired fibrinolysis may contribute to the prothrombotic state in these patients.